BF3 Mediated [1, 5]‐Hydride Shift Triggered Cyclization: Thioethers Join the Game. Issue 25 (1st July 2022) - Zaitseva, Elvira R.; Smirnov, Alexander Yu.; Timashev, Vladimir I.; Malyshev, Vadim I.; Zhigileva, Ekaterina A.; Mikhaylov, Andrey A.; Medvedev, Michael G.; Baleeva, Nadezhda S.; Baranov, Mikhail S.
Abstract: 2‐(2‐(Benzylthio)benzylidene)malonates can undergo the 1, 5‐hydride shift triggered cyclization resulting in thiachromanes in 45–84 % yield. Boron trifluoride as a reaction promotor is the key to success. DFT calculations revealed that the reaction proceeds via a chelate BF2 complex, which was confirmed by NMR‐analysis. Experimental and theoretical comparison of nitrogen, sulfur and carbon analogues revealed that sulfur derivatives have the highest activation barrier for the hydride transfer due to the unfavorable transition state geometry, which explains the lack of previous reports on 1, 5‐hydride shifts in (alkylthio)styrenes. Abstract : 1, 5‐Hydride shift triggered the cyclization of 2‐(2‐(benzylthio)benzylidene)malonates to thiachromanes, which are presented for the first time. Boron trifluoride as a reaction promotor is the key of this C−H activation success. Quantum chemical calculations have shown that the studied reaction proceeds via a O–BF2 –O chelate, which was confirmed by NMR‐analysis.